2022
DOI: 10.3390/ijerph191610042
|View full text |Cite
|
Sign up to set email alerts
|

Food Security as Ethics and Social Responsibility: An Application of the Food Abundance Index in an Urban Setting

Abstract: High levels of food insecurity signal the presence of disparities and inequities in local food access that have been shown to negatively impact the health and well-being of individuals and communities. Some argue that the lack of healthy, affordable and culturally relevant food within a community represents a troubling social and ethical concern for any society. The current research conducts an assessment of a specific community utilizing the framework outlined by the Food Abundance Index (FAI) scorecard. Comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This study revealed that there were a series of food outlets in Pittsburgh communities that did not have sufficient access via public transportation [33]. This study also implicated that for future research, it is necessary to account for environmental structures like bridges and highways that may impede travel to grocery outlets [33].…”
Section: The Food Abundance Indexmentioning
confidence: 88%
See 2 more Smart Citations
“…This study revealed that there were a series of food outlets in Pittsburgh communities that did not have sufficient access via public transportation [33]. This study also implicated that for future research, it is necessary to account for environmental structures like bridges and highways that may impede travel to grocery outlets [33].…”
Section: The Food Abundance Indexmentioning
confidence: 88%
“…The access dimension scale examined the accessibility of local grocery stores via public transportation, where a grocery store with a bus stop within a quarter mile was considered to be accessible [2]. Previous research used three of the five dimensions of the Food Abundance Index were assessed within the mid-Monongahela valley of Pittsburgh [33]. This study revealed that there were a series of food outlets in Pittsburgh communities that did not have sufficient access via public transportation [33].…”
Section: The Food Abundance Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, from the breadth and depth of research, as an important grain crop production base in China, the main maize-producing areas are responsible for the major task of ensuring national food security and the balance between supply and demand of agricultural products. With the rising food consumption level of residents in the new era, the main producing areas, the main marketing areas, and balanced production and marketing areas are working together to enhance the comprehensive grain production capacity (Murrell et al, 2022;Skawińska and Zalewski, 2022;Stavi et al, 2022;Teeuwen et al, 2022). How can the interests of the three regions be balanced?…”
Section: Limitations Of the Study And Future Researchmentioning
confidence: 99%
“…Although larger sample sizes are more feasible in cross-sectional and observational studies, which tends to improve the generalizability of the findings with a more diverse and robust population, this study design limits causal inferences. Additionally, inducing FI for research purposes would be considered unethical, as food is considered a basic human right, resulting in a dearth of randomized controlled trials to elucidate the cause-and-effect relationship of FI on health outcomes [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%